Using a One Health Case-Based Investigation for Improved Control of Brucellosis in Isiolo, Kenya - Karlsson, Philip A.; Persson, Carolina; Akoko, James; Bett, Bernard; Lundkvist, Åke; Lindahl, Johanna F. (Frontiers in Tropical Diseases, 2021)
Brucella is a highly pathogenic bacteria endemic in Kenya, and in spite of its severity in humans, the highly inadequate Febrile Antigen Brucella Agglutination Test (FBAT) remains a primary tool for diagnosis. Blood samples were collected from febrile patients in Kinna health center and screened by local routine. Milk samples were purchased from local milk hawkers and analyzed for Brucella antibodies using the milk ring test (MRT). The MRT-positive milk was traced to farms, and lactating cattle were sampled for milk and blood. Milk was MRT-tested and serum was analyzed using the Rose Bengal test (RBT) and iELISA. Available patient and farm samples were stored on FTA cards for qPCR analyses. Despite a limited sample size, our study in line with previous reports shows a low diagnostic sensitivity (67%) and specificity (40%) of FBAT when compared to qPCR. As many as 48% of raw bulk cattle milk samples were MRT-positive for Brucella antibodies and 60% of cattle on three visited farms were IS711 qPCR-positive. This case-based One Health investigation confirms the suspected Brucella presence, suggests targeted vaccination at high-prevalence farms, urgent interventions on milk safety and a re-evaluation of the diagnostic and treatment regime.